Low birth weight and its association with attention deficit hyperactivity disorder (ADHD) in young children - Bunga Astria Paramashanti; Rosma Fyki Kamala; Dwi Nur Rahmawati (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
This study was conducted to understand the association between low birth weight and attention deficit hyperactivity disorder (ADHD) in young children aged 36 – 59 months in Sedayu Subdistrict, Bantul District, Daerah Istimewa Yogyakarta. This study used cross-sectional design with a total of 185 children aged 36 – 59 months were selected by probability proportional to size (PPS) sampling technique. This study was located in Sedayu Subdistrict, Bantul District, Daerah Istimewa Yogyakarta. The study was conducted January 2017. Main variables in this study were low birth weight, prematurity, and attention deficit hyperactivity disorder (ADHD). Maternal and child book was used to confirm the birth weight and gestational age data. Abbreviated Conners Rating Scale form was used to detect ADHD symptoms in young children, followed by a psychologist confirmation. Data were analyzed by using descriptive statistics, chi-square test, and multiple logistic regression at 0.05 level of significance. The proportion of attention deficit hyperactivity disorder (ADHD) was 29.2% in this study. Meanwhile, the prevalence of low birth weight (<2500 g) was 8.11% and prematurity (<37 weeks gestational age) was 2.16%. Children with birth weight less than 2500 g were more likely to develop ADHD symptoms (OR: 3.2; 95%CI: 1.09-9.48) compared to children with normal birth weight. On the other hand, prematurity was not associated with ADHD (OR: 0.64; 95%CI: 0.06-6.89). This study concluded that low birth weight was associated with attention deficit hyperactivity disorder (ADHD). However, prematurity was not related significantly with ADHD. Efforts are needed in improving nutrition adequacy for infants and young children, also development stimulation, especially for those born with low birth weight.